Therapeutic potential of short-chain fatty acids for acute lung injury: a systematic review and meta-analysis of preclinical animal studies - Xie, Liying; Wang, Linyan; Liao, Yongxin; Yao, Miaoen; Mai, Tong; Fan, Rongrong; Han, Yun; Zhou, Gengbiao (Frontiers in Nutrition, 2025)
BackgroundShort-chain fatty acids (SCFAs), derived from the fermentation of dietary fiber by intestinal commensal bacteria, have demonstrated protective effects against acute lung injury (ALI) in animal models. However, the findings have shown variability across different studies. It is necessary to conduct a comprehensive evaluation of the efficacy of these treatments and their consistency.ObjectiveThis systematic review and meta-analysis aimed to explore the effects of SCFAs on ALI based on preclinical research evidence, in order to provide new treatment strategies for ALI.MethodsWe included studies that tested the effects of SCFAs on ALI in animal models. This study was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search for relevant studies was conducted in the PubMed, Embase, Web of Science, Cochrane Library, and China National Knowledge Infrastructure (CNKI) databases up to February 2024. The data were extracted in accordance with the established selection criteria, and the risk of bias was evaluated for each study.ResultsA total of 16 articles were finally included in the meta-analysis. The results indicated that the SCFAs significantly reduced lung wet-to-dry weight (SMD = −2.75, 95% CI = −3.46 to −2.03, p < 0.00001), lung injury scores (SMD = −5.07, 95% CI = −6.25 to −3.89, p < 0.00001), myeloperoxidase (SMD = −3.37, 95% CI = −4.05 to −2.70, p < 0.00001), tumor necrosis factor-alpha (SMD = −3.31, 95% CI = −4.45 to −2.16, p < 0.00001) and malondialdehyde (SMD = −3.91, 95% CI = −5.37 to −2.44, p < 0.00001) levels in animal models of ALI. The results of the subgroup analysis indicated that the efficacy of SCFAs varies significantly with dosage and duration of treatment.ConclusionSCFAs can reduce inflammation and oxidative stress in animal models of ALI. The clinical efficacy of SCFAs for ALI deserves further in-depth research.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=584008, CRD42024584008.